Dibalik Pengaruh Sebuah Pesan di Media - Widyokusumo, Lintang (Bina Nusantara University, 2011)
The inserting power of a message into the minds of recipients can be done through various stages of processing and filters contained in each individual recipient. It is a distinctive strength when designers can learn the process so that designing a work of visual design can be conveyed with both in the minds of society ast targets and generate action / feedback is expected. Article analysis the process of how a message in a media was able to convey the reader or viewers. The research was done by doing library research. It can be concluded that feeling, thinking, and actioning are process that influence people in understanding a message in a media.